Mempelajari Pertumbuhan dan Hasil Dua Belas Jenis Tanaman Microgreens - Ramdaniati, Ade Elsa; Wijana, Gede; Sukewijaya, I Made; Santosa, I Gusti Ngurah; Darmawati, Ida Ayu Putri (Agrotrop : Journal on Agriculture Science; Vol 15 No 1 (2025), 2025)
Studying the growth of Microgreens of twelve types of plants . The lack of information about the cultivation of microgreens, so it is necessary to conduct research related to the growth of microgreens in several types of microgreens plants. The purpose of this study is to find out the growth and yield of twelve types of microgreens plants. This experiment used a one-factor and three-test complete randomized design (CRD). The seeds of twelve types of microgreens plants are planted on cocopeat planting media. The types of plants are basil, broccoli, cilantro, green mustard, lemon basil, peashoot, green radish, red amaranth, red cabbage, red radish, shiso green and sunflower. The implementation of research includes the preparation of planting media, preparation of microgreens racks, planting, maintenance and harvesting. Variables of research include the percentage of cotyledon rupture, the percentage of radicula growth, the percentage of plumula growth, the percentage of growing leaves, germination, the day the cotyledons come to the surface of the medium, the percentage of growth, the length of the stem of microgreens, and the economical fresh weight of microgreens per plant. The results showed that the treatment of twelve types of microgreens plants grew well in cocopeat media. Each of them has a germination percentage above 80%, and differs only in terms of yield. Based on the aspect of the harvest, peashooot microgreens are different from other microgreens because they can be harvested many times, while other microgreens can only be harvested once.